1992
DOI: 10.14430/arctic1413
|View full text |Cite
|
Sign up to set email alerts
|

Energy Flow through the Marine Ecosystem of the Lancaster Sound Region, Arctic Canada

Abstract: This paper synthesizes the trophic dynamics of a Canadian arctic marine ecosystem in so far as it is known, using new data on primary production, zooFlankton, the bivalve Mya truncata, and arctic cod (Boreogadus saida), as well as literature values for marine mammals and seabirds. The 98 000 km reglon has a high rate of primary production relative to other parts of arctic Canada. About 60 g Cm-' are fixed annually, of which approximately 90% is contributed by phytoplankton, 10% by ice algae, and 1% by kelp. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
188
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(193 citation statements)
references
References 72 publications
5
188
0
Order By: Relevance
“…truncata has a wide, circumboreal distribution. It is a key species in food webs in arctic habitats (Welch et al 1992). In Europe, M. truncata is common along the entire coastline of the United Kingdom and Ireland, and down further south to Biscay (Willmann 1989;Ballerstedt 2001).…”
Section: Species Descriptionmentioning
confidence: 99%
“…truncata has a wide, circumboreal distribution. It is a key species in food webs in arctic habitats (Welch et al 1992). In Europe, M. truncata is common along the entire coastline of the United Kingdom and Ireland, and down further south to Biscay (Willmann 1989;Ballerstedt 2001).…”
Section: Species Descriptionmentioning
confidence: 99%
“…Harwood and Stirling 1982), they are not often seen to be part of "feeding frenzies" involving other cod predators such as harp seals (Phoca groenlandica), narwhals (Monodon monoceros) and white whales (Delphinapterus leucas) (Bradstreet et al 1986:27). Welch et al (1993) estimated that 60% of the annual diet of ringed seals in the Resolute area consisted of polar cod (also see Welch et al 1992), but they observed few ringed seals associated with cod schools. A notable exception was an occasion in Allen Bay (southern Cornwallis Island) in August when about 500 ringed seals were congregated, feeding on a large school of cod.…”
Section: Relations With Other Speciesmentioning
confidence: 99%
“…In turn, it is the staple of the seals, whales, and marine birds that account for many of the services provided by arctic marine ecosystems. This fish could effect as much as 75 % of the transfer of energy between the zooplankton and vertebrate predators (Welch et al 1992). Arctic cod inhabit the ice pack for part of their life cycle (Gradinger and Bluhm 2004) and form large overwintering aggregations at depth during the ice-covered season (Benoit et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Arctic cod inhabit the ice pack for part of their life cycle (Gradinger and Bluhm 2004) and form large overwintering aggregations at depth during the ice-covered season (Benoit et al 2008). Another ubiquitous consumer of copepods is the hyperiid amphipod Themisto libellula that funnels a significant fraction of the energy between the plankton and the higher trophic levels in ice covered seas (Dalpadado 2002;Welch et al 1992).…”
Section: Introductionmentioning
confidence: 99%